EFFECT OF MERCURY AND CADIMIUM ON THE BIOCHEMICAL PARAMETERS OF HYDRILLA PLANT: Life Science-Environmental Biology - C. DAS, GOUTAM; K. BIJAY KUMAR; B.K.MOHANTY (International Journal of Life Science and Pharma Research, 2013)
The metal phytotoxicity was examined taking two non-essential elements like mercury and cadmium on the aquatic hydrophytes like Hydrilla plant. Though the plants show toxicity symptoms in response to metal, they too are seen to develop resistance to the toxicity. To explore the possible recovery of the phytotoxicity of the test plant, growth hormone, kinetin was supplemented with the heavy metals in the experimentation. The total chlorophyll content in the test plant showed a decrease in content with the treatment of Hgcl2 and CdSO4 but, when these metal compounds were supplemented with kinetin showed significant recovery in the chlorophyll content. It was also observed that, mercury pronounced the level of toxicity in comparison to cadmium. In bimolecular studies like protein, Amino acid, sugar and nucleic acids (DNA and RNA) were studied. Protein, Sugar and DNA content in the treated plant showed a decrease in the act treatment and overall it was concentration dependant. In this case also Hgcl2 with Kinetin and CdSO4 with Kinetin reduced the toxicity of the metal to some extent in the plant. With reference to the days /periods of study, 10 days interval pronounced more stress conditions in the test plant, there by overall decline in the biochemical parameters